Indonesia’s Indigenous Suku Anak Dalam: knowledge for food and environmental sustainability - Ginting, Sadar; Wongta, Anurak; Ounjaijean, Sakaewan; Hongsibsong, Surat (Frontiers in Sustainable Food Systems, 2025)
This study provides an avenue for harnessing Indigenous knowledge to address contemporary environmental challenges by adopting traditional ecological knowledge and practices for food sustainability and environmental conservation. Based on primary field observations and interactions with the Indigenous Suku Anak Dalam (SAD) in Jambi Province, Indonesia, this study explores the significant potential of adapting Indigenous SAD traditional practices. These practices are deeply embedded and have great potential for adoption to address environmental challenges, including food insecurity and ecological degradation. These practices, which include selective harvesting, sustainable hunting, resource regeneration, and spiritual reverence for nature, align with key ecological theories and global conservation principles and demonstrate the wisdom of Indigenous knowledge in addressing contemporary environmental challenges by fostering biodiversity, maintaining ecological balance, and promoting responsible resource management. The emphasis on interconnectedness with nature and sustainable living strategies provides insights into achieving global sustainability goals, particularly in terms of food and environmental conservation. Integrating such Indigenous knowledge into modern conservation policies can yield culturally inclusive and ecologically effective solutions for global challenges. This study suggests that integrating traditional ecological practices into formal conservation frameworks can significantly improve biodiversity conservation and sustainable resource management. Policy-makers are encouraged to collaborate with Indigenous communities to develop inclusive environmental policies.